Fear, wonder, and science in the new age of reproductive biotechnology - Gilbert, Scott F., 1949-; Correia, Clara Pinto (Columbia University Press, 2017)
How does one make decisions today about in vitro fertilization, abortion, egg freezing, surrogacy, and other matters of reproduction? This book provides the intellectual and emotional intelligence to help individuals make informed choices amid misinformat.